A mensagem feminista de Belén de Sárraga e seus encontros com as lideranças do feminismo brasileiro - Lotúmolo Junior, José (Universidade Federal de São Carlos, 2025)
This research has analyzed the text from the Spanish lecturer, feminist and Free-Thinker Belén de Sárraga and her meetings with Brazilian feminist leaders. By means of documental research her texts and sources of information about her meetings in Brazil have been found out that her feminist ideas were aligned with the movements around the world and Brazil. The concepts by language researchers such as José Fiorin, Eni P. Orlandi, Mikhail Bakhtin, Valentin Volóchinov and Michel Foucault, have been used. The general objective was the analysis of Belén de Sárraga’s lectures and the highlighting of her particular marks in the texts that make them identified as feminist. Another objective has been her contact with Brazilian feminist leaders such as Julia Lopes de Almeida, Josephine Stefani Bertacchi, Cecília Meireles and Bertha Lutz. The goal is to contribute with gender studies on Science, Technologies and Society Field for better comprehension of the current situation through the affirmative movements of women at the beginning of the last century.

La presente investigación ha analizado los textos producidos por la oradora feminista y Libre-Pensadora española Belén de Sárraga y sus encuentros con lideres feministas brasileiras. Por medio del Levantamiento Documental sus textos han sido recuperados junto a las fuentes de información sobre su visita a Brasil. Utilizando Metodologías de Análisis del Discurso ha sido constatado que las ideas feministas de Belén de Sárraga estaban integradas a los movimientos alrededor del mundo y Brasil con las marcas del Libre-Pensamiento también presente. Fueran utilizados conceptos de estudiosos del lenguaje como José Fiorin, Eni P. Orlandi, Mikhail Bakhtin, Valentin Volóchinov e Michel Foucault. El objetivo general del estudio de las conferencias de Belén de Sárraga es la identificación de las marcas feministas en sus textos. También se confirmó en la trayectoria de sus viajes por Brasil sus contactos con líderes feministas brasileñas, entre las cuales se destacan Júlia Lopes de Almeida, Josephine Stefani Bertacchi, Cecília Meireles Bertha Lutz. De esta manera se espera contribuir con los estudios de género en el Campo Ciencia, Tecnología e Sociedad (CTS) para a partir de los movimientos de afirmación de la mujer en las primeras décadas del siglo pasado levantar una mejor comprensión del momento feminista actual.
Belén de Sárraga's feminist message and her meetings with the brasilian feminist leaders
Keywords: Belén de Sárraga; Livre-Pensamento; Feminismo; Júlia Lopes de Almeida; Josephine Stefani Bertacchi; Cecília Meireles; Bertha Lutz; Free-Thinking; Feminism; Libre-Pensamiento; CIENCIAS SOCIAIS APLICADAS; CIENCIAS HUMANAS; CIENCIAS HUMANAS::HISTORIA::HISTORIA DO BRASIL::HISTORIA DO BRASIL REPUBLICA; 5. Igualdade de Gênero; 10. Redução das Desigualdades